The Rhetorical Model of Selling Skintific Cosmetic Products Posted on TikTok - Rai Sahdai Suli; Warsidi Warsidi; Andi Samsu Rijal; Alfiandy Kamal (English Literature Studi Program Universitas Islam Makassar, 2025)
This study aims to examine the rhetorical model used in the promotion of Skintific beauty products on the TikTok platform. Employing a qualitative approach and a top-down method, this research analyzes 20 TikTok videos promoting Skintific products based on content relevance, view count, user engagement, and video duration. The analysis focuses on the rhetorical strategies and persuasive structures used to attract interest and increase consumer purchase intention. The results indicate that the appropriate use of a rhetorical model in promotional content on TikTok can enhance the appeal of Skintific products to consumers and influence their purchasing decisions. These findings provide important insights for marketing practitioners in designing effective communication strategies on social media. Keywords: Beauty product promotion, Persuasive strategies, Rhetorical model, Skintific, Social media marketing, TikTok